HIF1α/miR-520a-3p/AKT1/mTOR Feedback Promotes The Proliferation And Glycolysis Of Gastric Cancer Cells - Pan C; Liu Q; Wu X (Cancer Management and Research, 2019)
Chen Pan,1,2 Qi Liu,2 Xiaoling Wu1 1Department of Gastroenterology, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Gastroenterology, The Affiliated Hospital of Guizhou Medical University, Guiyang, People’s Republic of ChinaCorrespondence: Xiaoling WuDepartment of Gastroenterology, The Second Affiliated Hospital of Chongqing Medical University, Chongqing 400010, People’s Republic of ChinaTel +86 189 8511 5661Email gzykdxwxl123456@sina.comPurpose: Various microRNAs are involved in the development of gastric cancer (GC). This study investigated the role and mechanism of miR-520a-3p in GC.Method: Quantitative real-time fluorescence PCR (qRT-PCR) was applied to measure the expression level of miR-520a-3p in GC tissues and cell lines. The chi-squared test was employed to evaluate the relationship between the expression level of miR-520a-30p and clinical traits. The cell count kit-8 assay was used to detect the effect of miR-520a-3p on GC cell proliferation, while its effect on glycolysis was determined using the glucose assumption, lactate, and ATP production assay. The effect of miR-520a-3p on tumor growth in vivo was examined using a xenograft model. The relationship between miR-520a-30p and AKT1/mTOR/HIF1α pathway in normoxia and hypoxia was investigated using bioinformatics analysis, dual-luciferase reporter assay, qRT-PCR and Western blotting.Results: The expression of miR-520a-3p was decreased in GC tissues and cell lines. The expression level of miR-520a-3p was negatively associated with various malignant biological properties in patients. Overexpression/inhibition of miR-520a-3p decreased/promoted cell proliferation and glycolysis in vitro. Overexpression of miR-520a-3p inhibited tumor growth in vivo. AKT1 is the functional target of MiR-520a-3p, which was decreased in miR-520a-3p-overexpressing cells. In addition, overexpression of miR-520a-3p decreased the protein level of AKT1, mTOR, HIF1α, and target genes of HIF1α such as Glut1 and VEGF. Restoration of the expression of AKT1 can decrease the inhibitory effect of miR-520a-3p on the AKT1/mTOR/HIF1α pathway, as well as cell proliferation and glycolysis. Furthermore, the level of miR-520a-3p was decreased, while that of AKT1 was increased under hypoxia. Notably, inhibition of HIF1α or overexpression of miR-520a-3p suppressed these effects.Conclusion: Our study provided the first evidence for the existence of HIF1α/miR-520a-3p/AKT1/mTOR feedback, which promotes the proliferation and glycolysis of GC cells, highlighting a potential novel target for treatment.Keywords: gastric cancer, miR-520a-3p, AKT/mTOR/HIF1α pathway, glycolysis